Accuracy of Kirby-Bauer Susceptibility Tests Read at 4, 8, and 12 Hours of Incubation: Comparison with Readings at 18 to 20 Hours - Kluge, Ronica M. (1975)
Disk diffusion antibiotic susceptibility tests as performed by the hospital diagnostic microbiology laboratory were read at 4, 8, and 12 h of incubation and compared to the traditional 18-h readings. Both the zone size in millimeters and a judgement of susceptible or resistant were recorded by the investigator at each time interval for each drug tested against the various clinical isolates. Considerable variation of zone sizes existed for certain organisms (e.g., staphylococci and Proteus) and certain antibiotics (e.g., trimethoprim-sulfamethoxazole) when zone sizes in millimeters were examined. However, 8 to 60% of isolates demonstrated visible growth at 4 h of incubation and could be placed in susceptible or resistant categories with a fair degree of accuracy (74 to 95% agreement with 18-h readings). By 8 h of incubation, 83 to 100% of the cultures showed visible growth and almost all the organisms had accurate readings (89 to 98% agreement). The ability to determine antimicrobial susceptibility patterns early could influence favorably the prognosis in serious infections.